Motivation Of Students In Preventing Scabies At Islamic Boarding School - Arso Wibowo, Dodik; Nadya, Alma Ainun (Journal of Applied Nursing and Health, 2024)
Background:  Islamic boarding schools are a place for students to learn about Islam. The term santri is used for people who study religion at Islamic boarding schools. The students live together, usually students are often associated with scabies disease due to several factors, one of the factors that is suspected to be the cause is the lack of motivation in the students. Motivating students aims for students to be more concerned about cleanliness. This study aims to determine the motivation in preventing scabies.   Methods: The research design was quantitative descriptive, with a research population of 120 respondents and a sample of 55 respondents. Sampling techniques with Purposive Sampling. The research was carried out from March 18 to April 30, 2024 at the Darunnjaah Islamic Boarding School with the variables of student motivation in preventing scabies. The research instrument with a data questionnaire was analyzed with percentages, interpreted quantitatively Results: Based on the results of research from 55 respondents, most of the respondents had a strong motivation as many as 37 respondents (67%) and almost half of the respondents had moderate motivation as many as 18 respondents (33%) in preventing scabies. Conclusion: The motivation of students in preventing scabies is influenced by several factors, namely gender, age, length of time students have lived in Islamic boarding schools, have received information about scabies and sources of information. It is hoped that the students will be more cooperative in seeking information related to scabies disease and its prevention to increase student motivation in preventing scabies and it is expected that the Islamic boarding school will often provide information about scabies disease and its prevention.